(untitled) (Al-Qamar, 2022)
The present research was administered at the grassroots level investigated the perceptions of madrasa teachers as well as the students about the challenges of modern education in madrasas. The researcher intends to examine their perceptions to explore the challenges in imparting the modern education and its possible suggestions which might be helpful in imparting better modern education and enhance the standard of modern education in madrasas of Pakistan. Qualitative method was used in the study. Multistage sampling technique was applied to select the desired sample. At the first stage, 3 madrasas were selected conveniently where modern education in being provided along with routine darse-nizami course. At the next stage, total 18 participates (9 teachers and 9 students of undergraduate level) were taken from 3 madrasas. The qualitative data were collected through two separate open ended interview questionnaires for madrasa teachers and students respectively. For the analysis of qualitative data, thematic analysis was done. Thematic analysis revealed that majority of the madrasa teachers as well as the students inclined towards incorporating modern education into the madrasa curriculum. Major challenges were found as extensive syllabus, diversion of student’s concentration, learning burdens, overburden stress, autocratic administration and it’s attitude, insufficient learning resources, lack of teachers, inconveniences between madrasa and board/ university academic calendar. It was recommended that Integration of modern and madrasa education should be at the subject level. In regular darse nizami group, modern languages and subjects may be included by excluding unnecessary and very old subjects. The government should allocate some budget to promote modern education as well as to meet the shortage of learning resources and faculty of modern subjects in madrasas.